Studies Of the Physico-Chemical Parameters of Fish Farm Water in Antsirabe I, Vakinankaratra Madagascar - Rabarison Rindra; Ramanambe Ravelomanantsoa Nicole; Rabeharitsara Andry Tahina; Koto-te- Nyiwa Ngbolua (Britain International for Academic Research (BIAR) Publisher, 2024)
This study examines the quality of water used to farm tilapia and carp in Antsirabe, Madagascar. The physico-chemical parameters of 95 farm sites were analysed to determine and assess their compliance with the quality standards required for sustainable aquaculture. Samples taken at several farm sites revealed an average pH of 6.92, an average conductivity of 105µS/cm, an average oxygen level of 6mg/l, a temperature of 22°C and an average salinity of 0.054/00. These results highlight the importance of water quality management in aquaculture practices in Antsirabe, helping to ensure the economic and environmental viability of fish farming in this region.